Experimental and Simulation Studies on Nitrogen Dynamics in Unsaturated and Saturated Soil Using HYDRUS-2D. (2016) - Mekala, C.; Nambi, Indumathi M.
Abstract: Effective irrigation practices have become an optimal means of providing water and nutrients to crops as well as preventing the vulnerability of ground water contamination. This could be achieved by understanding the fate and transport processes of nitrogen compounds in the subsurface. However, nitrogen dynamics in the plant rhizosphere is very complex, which depends on many factors such as soil temperature, pH, water content, soil microbes, soil type and plant characteristics and cannot be easily quantified. Using state-of-the-art modelling techniques, an attempt was made to evaluate the reactive transport of ammonium nitrogen under continuous and alternate wetting and drying mode (AWD) of irrigation in soil columns using a HYDRUS 2D model. The model quantifies the soil sorption, microbial transformations such as nitrification and denitrification, leaching, and final release to aquifer for ammonium and nitrate input fluxes. This quantification helped in designing an optimal fertigation and irrigation schedule. Soil column study was done with variable saturation and in a combined unsaturated (45cm) and saturated (5cm) representing vadose and aquifer. Drip irrigation with wastewater containing 100mg/L of ammonium and 500mg/L of organic carbon (acetate) was applied based on the recommended total quantity of nutrients in continuous and pulse modes to the column. The soil parameters, initial and boundary conditions used in the model were obtained through experimental studies. The HYDRUS-2D model was developed, calibrated and validated with experimental results. The model performed could predict well the experimental data. Under continuous irrigation, nitrification (0.23/d) was the predominant process whereas both nitrification and denitrification occurs simultaneously in AWD with the overall nitrate removal efficiency of 60%. Consequently, the scenario prediction using this model for optimal fertigation schedule was done for groundnut crop. Further this model could be extended for various scenario predictions for designing optimal irrigation-fertigation schedules for sustainable agricultural practices.